2010
DOI: 10.1039/b916579g
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) and palladium(II) metallomacrocycles derived from cationic 4,4′-bipyridinium, 3-aminopyrazinium and 2-aminopyrimidinium ligands

Abstract: A series of cationic, ditopic N-donor ligands based on 4,4¢-bipyridine (4,4¢-bipy), 3-aminopyrazine (apyz) and 2-aminopyrimidine (apym), each incorporating two positively-charged N-heterocycles linked by a conformationally-flexible spacer unit, have been synthesised and treated with palladium(II) or platinum(II) precursors [M(2,2¢-bipy) 4 . When the cationic apyz or apym ligands were used in aqueous solution, the analogous metallomacrocycles did not form. Instead, deprotonation of the exocyclic amino group oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…[5] More recently, the biological properties of these metallacyclic structures have also begun to emerge. Metallacycles [6] and helicates [7] have been found to interact with DNA, while other architectures have been shown to be cytotoxic to cancer cells and bacteria. [8] …”
Section: Introductionmentioning
confidence: 99%
“…[5] More recently, the biological properties of these metallacyclic structures have also begun to emerge. Metallacycles [6] and helicates [7] have been found to interact with DNA, while other architectures have been shown to be cytotoxic to cancer cells and bacteria. [8] …”
Section: Introductionmentioning
confidence: 99%
“…Extensive stacking may also result in emission at lower energies (typically > 800 nm) corresponding to 3 MMLCT excited states. [52,56,57,[62][63][64][65][66][67][68][69][70][71] The impact of CB[n]e ncapsulationo nt ransition energies varies greatly, with bathochromic shifts being typically more common than hypsochromic ones. [72][73][74][75][76][77] Shifts result from a combination of competitive factors:( 1) as shown by Nau and co-workersi nt he case of 2,3-diazabicyclo-[2.2.2]oct-2-ene and its n!p*transitions, [78] adecrease in the environment polarizability from the solvent to the cavity of CB [7] causes hypsochromic shifts; [79] (2) as shown by Biczóka nd co-workersint he case of berberine (1), [77] ad ecrease in the orientation polarizability parameter of the environment (that has both ap olarity and a polarizability term) causesb athochromic shifts from water to CB [7].O ne shoulda lso note that while the CB [7] cavityh as low polarities and polarizabilities, Kaifer and co-workers recently showed that the polarity of the environment surrounding the carbonyl rims of CB [7] is in fact more polar than water; [80] the impact of this specific environmento nt he optical properties of chromophores is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Emissions typically originate from the 3 [π(C≡CR)→π*(tpy)] and 3 [dπ(Pt)→π*(tpy)] transitions. Extensive stacking may also result in emission at lower energies (typically >800 nm) corresponding to 3 MMLCT excited states …”
Section: Resultsmentioning
confidence: 99%
“…Complexes 8·8NO 3 and 9·8NO 3 were prepared as described previously. 14 The 16-mers D2a, D2b (Geneworks, HPLC grade) were purified using HPLC (aqueous NH 4 OAc→MeCN gradient) as reported previously. 35 In each case, equimolar quantities 36 of the appropriate strands (both dissolved in 0.1 M NH 4 OAc, pH 7.4) were combined to give a mixture in which the concentration of each of these constituents was 1 mM (values for [ssDNA] were estimated by measurement of UV absorbance at 260 nm using e 260 values for A, G, C and T of 15200, 12010, 7050 and 8400 M -1 cm -1 , respectively).…”
Section: Methodsmentioning
confidence: 99%
“…8 8+ and 9 8+ , containing ligands that incorporate two positivelycharged N-heterocycles linked by a conformationally-flexible spacer unit. 14 These metallomacrocycles possess high aqueous solubility and charge and contain cavities which are semi-rigid and of nanoscale dimensions. The DNA-binding characteristics of both these classes of complexes with double-and single-stranded DNA (dsDNA and ssDNA, respectively) were investigated using ESI-MS and thermal denaturation experiments.…”
Section: Introductionmentioning
confidence: 99%